Real interest rates and the cost of capital - Jenkinson, T (1999)
The real interest rate and the equity risk premium are critical economic parameters that influence a wide range of economic decisions. This paper considers the problems involved in estimating expected real interest rates and the equity risk premium, and hence the overall cost of capital. Using UK data, it suggests reasons why estimates based on historical returns may be misleading, and discusses alternative approaches to estimating the cost of capital.